Optimizing Power Grid Stability with Enhanced Circuit Breaker Maintenance: Mengoptimalkan Stabilitas Jaringan Listrik dengan Pemeliharaan Pemutus Sirkuit yang Disempurnakan - Cahyo, Chandra Darmawan Dwi; Ayuni, Shazana Dhiya (Procedia of Engineering and Life Science, 2024)
This study aims to evaluate the effectiveness of maintenance techniques on 20 kV Power Circuit Breakers (PMTs) using the Research and Development (R&D) method. Key performance variables assessed included contact resistance, PMT synchronism, and insulation resistance. Findings revealed that contact resistance for all phases was below 100 µΩ, indicating optimal connectivity. Synchronism testing showed time differences of 0.7 ms during opening and 1.05 ms during closing, both within acceptable limits. Furthermore, insulation resistance exceeded the 20 MΩ standard, confirming the insulation's integrity. These results suggest that regular maintenance using precise measurement techniques ensures the continued reliability and safety of MV electrical delivery systems. Highlights: Rising Electricity Demand: PT PLN (Persero) faces increasing electricity needs. Advanced Protection Solutions: Innovative equipment addresses conventional limitations. Research Insights: Findings ensure safety and reliability in medium voltage systems. Keywords: Contact Resistance, Insulation Resistance, PMCB, Synchronism Testing